Throughput analysis of full-duplex communication cognitive radio network - Lodro, Mir Muhammad; Greedy, Steeve; Mahoto, Naeem A.; Unar, Mukhtiar A. (Springer, 2017)
In this paper we deal with the throughput of full-duplex cognitive communication radio which exploits unused band of primary user (PU) network. Classical cognitive radio uses half-duplex communication spectrum sensing to perform spectrum sensing and data transmission at different time intervals. It’s well-established fact that in half-duplex communication cognitive radio spectrum sensing time increases at low SNR which gives rise to lesser data transmission time for secondary user (SU) and hence results in less throughput for SU. It’s useful idea to do spectrum sensing and data transmission at the same time with two different antennas co-located on the SU transceiver. This shall not only guarantee high probability of detection of PU but also increased data transmission which means more throughput for SU. However, simultaneous sensing and data transmission has inherent problem of self-interference. One of the possible solution is to use polarisation discrimination in which sensing and data transmission antennas must use different polarisation. This is feasible if there is prior information about the polarisation of the signals emitted by the PUs. It shall be of special interest to assess throughput using analytical expressions for probability of detection PD, probability of false alarm PFA at various values of SNR for time-slotted cognitive radio which uses half-duplex spectrum sensing and non-time-slotted cognitive radio which uses full-duplex communication cognitive radio.